The Consistency of the Sufficiency Economy Philosophy (SEP) with Sustainable Development Goals (SDGs) - Wongkumchai, Tachakorn; Na Ayuthaya, Smitti Darakorn; Kiattisin, Supaporn (Journal of Mobile Multimedia, 2020)
The purpose is to find the consistency of the SEP with SDGs. The sample used in this research was from development projects based on the application of the SEP with the total of 1,677 projects. These 1,667 projects were compared to the Taro Yamane table at a 95% confidence level with a deviation of 0.02. In addition, the sample of 10 projects under the framework of South-South cooperation and the Triangular cooperation were purposively selected. Questionnaires were used as the research tools to obtain opinions of experts consistency of the SEP to the dimensions of economic, social, and environmental development with the SDGs. The accuracy of the questionnaires is 0.88. The data were analyzed using Decision Matrix Analysis, Pearson’s correlation, percentage, and average. The results showed that sustainable development based on the application of the SEP was consistent with SDGs in 3 dimensions: environmental at 28.40% ( = 4.73), economic at 27.14% ( = 4.52), and social at 26.08% ( = 4.35). The SEP is positively consistent with SDGs at 42.33% (r = 0.42325), which suggests that more implementation of development projects in accordance with the SEP leads to more development towards SDGs in each dimension.